Efficacy and Safety of Chinese Medicine Lianhua Qingwen for Treating COVID-19: An Updated meta-Analysis - Li, Yapeng; Xiao, Peng; Liu, Nanyang; Zhang, Zhijie (Frontiers in Pharmacology, 2022)
The traditional Chinese medicine formula Lianhua Qingwen (LQ) combined with western medicine therapy is beneficial to coronavirus disease-19 (COVID-19), but there is still a lack of strong evidence-based. We conducted a systematic review and meta-analysis to evaluate the efficacy and safety of LQ combined with western medicine for patients with COVID-19. Seven databases (Chinese and English) were searched by two independent reviewers. Search for relevant keywords such as “Chinese medicine”, “Chinese herbal medicine”, and “Lianhua Qingwen” in the titles and abstracts of articles retrieved in the databases. Randomized controlled trials or case-control studies that reported sufficient data of participants before and after the intervention were included. Two researchers independently reviewed the studies and extracted the data. Fixed-or random-effect model was used to calculate the overall pooled risk estimates. Forest plots were generated to show pooled results. Seven studies involving 916 participants were included in the meta-analysis. Overall, compared with the control group, the total efficacy (OR = 2.23, 95% CI 1.56, 3.18), adverse events (OR = 0.42, 95% CI 0.18, 0.97), chest computed tomography manifestations (OR = 1.74, 95% CI 1.12, 2.72), and aggravation rate of conversion to severe cases (OR = 0.47, 95% CI 0.30, 0.75) of the intervention group were better. Moreover, the intervention group has an advantage over the control group in improving clinical symptoms (fever, cough, fatigue, chest tightness, shortness of breath, and expectoration) and shortening the fever duration (P0.05). Our findings indicate that LQ combined with western medicine may be more effective in treating COVID-19. However, due to the urgency of SARS-CoV-2 outbreaks leading to low methodological quality and not rigorous designs. This meta-analysis cannot draw clear conclusions.